1991
DOI: 10.1111/j.1365-2796.1991.tb00371.x
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of recurrence and hypothyroidism following treatment with antithyroid drugs, surgery or radioiodine in all patients with thyrotoxicosis in Malmö during the period 1970–1974

Abstract: The incidence of recurrence and of hypothyroidism was determined in all new patients treated for thyrotoxicosis during the period 1970-1974 in an unselected, well-defined urban population. A total of 309 patients were followed up for a median time period of 108 (1-192) months. There was a cumulative incidence of 51% recurrence in patients who were treated with antithyroid drugs for Graves' thyrotoxicosis, whereas after surgery or radioiodine treatment there were few recurrences, but 32% and 78% cumulative inci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 36 publications
(3 reference statements)
1
20
1
Order By: Relevance
“…Swedish studies from the 1970s and 1980s report somewhat higher relapse rates than our study (7,20) even though definite ablative methods were used more frequently, and that would supposedly lead to fewer and more easily ATD-treated patients at that time. However, TRAb methods are more sensitive today (26), probably affecting the number of patients diagnosed with GD by such assays, as used in 2004 in our study, and may have a better prognosis with ATD.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…Swedish studies from the 1970s and 1980s report somewhat higher relapse rates than our study (7,20) even though definite ablative methods were used more frequently, and that would supposedly lead to fewer and more easily ATD-treated patients at that time. However, TRAb methods are more sensitive today (26), probably affecting the number of patients diagnosed with GD by such assays, as used in 2004 in our study, and may have a better prognosis with ATD.…”
Section: Discussioncontrasting
confidence: 44%
“…Only a few small observational studies from the 1970s and 1980s have reported on the prognosis after ATD treatment in Sweden, and only a minority of the eligible patients had been treated with ATDs (7,19,20). The cumulative relapse rates were 44-53%.…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of hypothyroidism varies from 0% to 36% in different surveys (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). The main factors that have been associated with occurrence of hypothyroidism after 131I therapy in patients with solitary autonomous thy-roid nodules are: nonsuppressed serum TSH, 131I uptake in the paranodular tissue, thyroid autoantibodies, and the size of 131I dose.…”
Section: Discussionmentioning
confidence: 99%
“…In previous investigations of the effect of 131I treatment on autonomous solitary thyroid nodules, only a minority received antithyroid medication prior to 131I therapy (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). The aim of this study was to investigate changes in the thyroid 99mTc-pertechnetate scintigram related to normalization of serum TSH with antithyroid drugs before and after subsequent 131I therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Current therapies for Graves' disease consist of antithyroid drugs, radioiodine and surgery (4). Antithyroid drugs, which are usually prescribed for at least 1 year, are associated with a sustained remission in only 30-40% of patients after 10 years (5,6). In addition, these drugs are accompanied by rare side effects, the most important being agranulocytosis and hepatic failure (6).…”
Section: Introductionmentioning
confidence: 99%